1999
DOI: 10.1071/ar99004
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal acetogens and their potential to lower ruminant methane emissions

Abstract: Ruminant methane is a major contributor to the anthropogenic greenhouse gas inventories of Australia and New Zealand. Direct intervention in the rumen offers one means for controlling ruminant methane emissions. In this respect, acetogenic bacteria (acetogens) normally present in the rumen are of interest because they have the potential to provide an alternative sink for H2, an essential intermediate in the formation of methane. Although little is known about the populations of acetogens in grazing ruminants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 41 publications
2
96
0
7
Order By: Relevance
“…Creating conditions to support the growth of reductive acetogens is a further strategy for maintaining a low partial pressure of H 2 at the fermentative sites in the rumen digesta (Joblin 1999). However, in the rumen, methanogens usually outcompete acetogens for H 2 .…”
Section: Reductive Acetogenesismentioning
confidence: 99%
“…Creating conditions to support the growth of reductive acetogens is a further strategy for maintaining a low partial pressure of H 2 at the fermentative sites in the rumen digesta (Joblin 1999). However, in the rumen, methanogens usually outcompete acetogens for H 2 .…”
Section: Reductive Acetogenesismentioning
confidence: 99%
“…This suggests that acetogens may serve as hydrogen sinks in experiments, which seek to lower methane emissions (van Nevel and Demeyer, 1995;Morvan et al, 1996;Joblin, 1999) in cattle. Joblin et al (1999) has reported that methane production decreased by 97% and 64%, respectively, when a Methanobrevibacter smithii sp. isolated from a grazing sheep was grown on H 2 /CO 2 in vitro in the presence of a rumen acetogen isolate.…”
Section: Introductionmentioning
confidence: 99%
“…Reductive acetogens are a group of bacteria that can produce acetate from hydrogen and carbon dioxides (4H 2 +2CO 2 →CH 3 COOH+2H 2 O) using the acetyl-CoA pathway (Drake et al, 2006). This suggests that acetogens may serve as hydrogen sinks in experiments, which seek to lower methane emissions (van Nevel and Demeyer, 1995;Morvan et al, 1996;Joblin, 1999) in cattle. Joblin et al (1999) has reported that methane production decreased by 97% and 64%, respectively, when a Methanobrevibacter smithii sp.…”
Section: Introductionmentioning
confidence: 99%
“…Effectively, it is wasted feed material and energy that could otherwise be available for animal production. If methanogenesis were reduced in the rumen and the carbon was captured by other mechanisms, such as reductive acetogenesis, this would represent an energetic gain of 4--15% to the animal (Nollet et al 1997;Joblin 1999). Ruminal methane is generated by a diverse group of microorganisms within the Domain Archaea.…”
Section: Introductionmentioning
confidence: 99%